EFFECTS OF AMLODIPINE AND BISOPROLOL ON CAROTID AND VERTEBRAL BLOOD FLOW IN PATIENTS WITH ARTERIAL HYPERTENSION - E. D. Golovanova; N. N. Silaeva; D. Y. Kovalev (Столичная издательская компания, 2016)
Aim. To compare influence of amlodipine and bisoprolol on peripheral vascular resistance (PVR) in carotid and vertebral arteries in elderly and senile men with arterial hypertension (HT) and ischemic heart disease (IHD).Material and methods. 135 patients aged 35-90 y.o. were examined. PVR was determined by Doppler ultrasound in common (CCA) and internal (ICA) carotid arteries as well as vertebral artery (VA). Vascular remodeling was evaluated by volume sphygmography. The influence of the monotherapy with amlodipine or bisoprolol (2,5-5 mg once daily) on PVR in 54 patients of elderly and senile age with isolated systolic HT 1-2 degrees and IHD.Results. Therapy with amlodipine decreased of peripheral resistance of CCA, ICA in elderly and senile men with isolated systolic HT 1-2 stages and IHD. Monotherapy with bisoprolol did not increase in PVR of CCA, ICA.Conclusion. Amlodipine is effective antihypertensive drug with positive influence on pathogenetic mechanism of isolated systolic HT in elderly and senile patients.